Application of error-corrected sequencing technologies for in vivo regulatory mutagenicity assessment - Carole L. Yauk; Anthony M. Lynch; Vasily N. Dobrovolsky; Maik Schuler; Stephanie L. Smith-Roe; Devon Fitzgerald; Jake Higgins; Naveed Honarvar; Frank Le Curieux; Shoji Matsumura; Sheroy Minocherhomji; Leslie Recio; et al. (Regulatory Toxicology and Pharmacology, 2026)

Potato Cv. ‘Granola’ Has Moderate Tolerance for Bacterial Wilt Disease - Gashaw Belay Alemu; Jake A. Criscuolo; Charlie Higgins; Caitilyn Allen (American Journal of Potato Research, 2025)
Bacterial wilt or brown rot caused by Ralstonia solanacearum is among the most destructive diseases of potato in tropical highlands worldwide. There are no completely wilt-resistant varieties, but growers can reduce losses by planting partially resistant or tolerant potatoes. We screened the popular tropical potato cv. ‘Granola’ for bacterial wilt resistance under controlled conditions. Granola plants inoculated with high doses of R. solanacearum IIB-1 (Race 3 biovar 2) had reduced wilt disease progress relative to susceptible control cv. ‘Russet Norkotah’. Although the pathogen did colonize Granola plants, it reached significantly lower population sizes in Granola stems, stolons, and especially tubers than in those of Russet Norkotah. These results suggest that Granola has some tolerance to bacterial wilt, likely mediated by suppression of bacterial colonization. Thus, Granola could be a useful parent for tropical potato breeding programs.